Costa Rica local governments, organizational behavior and the human development capacities approach (Dissertare, 2021)
In this essay, it is postulated that the change in organizational behavior in Costa Rican local governments is considered a relevant variable to improve institutional performance, since it is related to the attributes of flexibility and proactivity of human talent, which are essential to manage the organization in the face of the changing environment, based on work environments characterized by the participation and a high degree of autonomy of the workers, in addition to the cooperation links between them. Because the municipal government bodies do not escape these challenges, this essay analyzes the capabilities approach as a body of postulates that stimulates changes in the organizational behavior of Costa Rican local governments, with a view to generating responses to the demands of the environment within the framework of human development. The focus of the work is qualitative with documentary design and the application of critical hermeneutics as a method of analysis. Among the conclusions of the essay, it is highlighted that in order to achieve changes in the organizational behavior of Costa Rican local governments, it is necessary to develop capacities that allow officials to internalize a shared prospective vision, both in what the institution should be in the long term, as in what concerning the attention to the needs of citizens.
Keywords: organizational behavior; human development; local governments; social capital; capabilities approach